1992
DOI: 10.1111/j.1755-3768.1992.tb02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance in antiamblyopia occlusion therapy

Abstract: Antiamblyopia occlusion therapy relies on compliance. We retrospectively reviewed the charts of 496 amblyopic subjects. Measures of non-compliance included patient reporting and patient records of broken appointments. Out of 496 subjects, 92 (18%) failed to follow the occlusion regimen. Compliance with treatment was analyzed by age group, refractive error and type of strabismus. The failure rate was 82.6% for the unilateral high myopia group and 37.5% for the monofixation syndrome group. The risk for non-compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 13 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…We selected this dichotomization because the visual acuity assessment at twelve months of age may have affected subsequent patching and because it has previously been observed that patching is higher in the first year of life than thereafter (18). We limited the analysis to children with at least three assessments in the first period and five in the second because, although reported patching is consistent over time (Cronbach’s Alpha >0.75), relatively large intra-individual differences were reported.…”
Section: Methodsmentioning
confidence: 99%
“…We selected this dichotomization because the visual acuity assessment at twelve months of age may have affected subsequent patching and because it has previously been observed that patching is higher in the first year of life than thereafter (18). We limited the analysis to children with at least three assessments in the first period and five in the second because, although reported patching is consistent over time (Cronbach’s Alpha >0.75), relatively large intra-individual differences were reported.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] Poor compliance with amblyopia therapy in unilateral high myopia has been reported in previous studies. 4,5,18 Hussein and coworkers, 14 reporting on 104 children with anisometropic amblyopia, found that poor initial visual acuity, lack of compliance, and age older than 6 years are risks for treatment failure.…”
Section: Discussionmentioning
confidence: 97%
“…Also, patching is used in strabismus as a non- surgical treatment. [5], [6] Many studies have demonstrated that treatment compliance is the most important factor for predicting a successful outcome in amblyopia [10], [12]–[15]. In an attempt to improve compliance, optical and pharmacological penalization were introduced and used [16][18].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors, such as patient’s age, initial visual acuity, refractive error and parental understanding, contribute to the compliance of eye patching. [10], [11] Nowadays, many brands of patches are available. However, there have been few investigations concerning the patch as a tool for occlusion therapy.…”
Section: Introductionmentioning
confidence: 99%